2020
DOI: 10.1016/j.stem.2019.12.015
|View full text |Cite|
|
Sign up to set email alerts
|

Interneuron Accumulation of Phosphorylated tau Impairs Adult Hippocampal Neurogenesis by Suppressing GABAergic Transmission

Abstract: Highlights d Phospho-tau is accumulated in DG GABAergic interneurons of AD patients and mice d Interneuron overexpressing human tau impairs adult hippocampal neurogenesis d Tau accumulation reduces GABA, disinhibits local circuits, and promotes astrogliosis d THIP, a d-GABA A R agonist, improves neurogenesis and cognition in AD mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 74 publications
4
90
0
Order By: Relevance
“…For instance, GSK-3β overactivation or accumulation might accelerate the depletion of NSC pool and impair AHN through inducing the hyperphosphorylation of tau, a microtubule-associated protein plays pivotal roles in shaping AHN 46 - 48 , since tau hyperphosphorylation has been widely accepted as one of hallmarks of accelerated aging and neurodegenerative diseases 49 . We have recently evidenced in a parallel study that accumulation of phosphorylated tau in GABAergic interneurons in the neurogenic niche induced AHN deficits, by disinhibiting local neural circuits and increasing NSC-derived astrogliosis 50 . However, whether and how tau hyperphosphorylation by GSK-3β in NSCs determines AHN, especially during accelerated senescence, remains unknown.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, GSK-3β overactivation or accumulation might accelerate the depletion of NSC pool and impair AHN through inducing the hyperphosphorylation of tau, a microtubule-associated protein plays pivotal roles in shaping AHN 46 - 48 , since tau hyperphosphorylation has been widely accepted as one of hallmarks of accelerated aging and neurodegenerative diseases 49 . We have recently evidenced in a parallel study that accumulation of phosphorylated tau in GABAergic interneurons in the neurogenic niche induced AHN deficits, by disinhibiting local neural circuits and increasing NSC-derived astrogliosis 50 . However, whether and how tau hyperphosphorylation by GSK-3β in NSCs determines AHN, especially during accelerated senescence, remains unknown.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, elimination of young adult-generated granule cells increases overall DG excitability [ 63 ] and gamma network activity [ 64 ]. Meanwhile, local PV+ interneurons in DG serve as a unique local circuit component to regulate hippocampal neurogenesis [ 65 , 66 ]. Thus, reduced PV+ interneurons in DG result in the loss of adult-generated neurons in poly (I:C) offspring, which further causes an increase in gamma oscillation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that pTau accumulates in the hippocampal subgranular cell zone and hilus in AD patients. Most of these pTau-positive cells have been identified as GABAergic interneurons by co-labeling with glutamate decarboxylase 67 (GAD67) in PV and SST neurons, further suggesting GABA inhibitory interneuron function is disturbed in AD ( Zheng et al, 2020 ). Compared with controls, GABA inhibitory interneurons and SST neurons in the brains of AD patients are abnormally reduced, along with the inhibitory neurotransmitters ( Bareggi et al, 1982 ; Zimmer et al, 1984 ; Grouselle et al, 1998 ; Bai et al, 2015 ; Shetty and Bates, 2016 ; Table 1 ).…”
Section: Targeting Increased Numbers Of Gaba Inhibitory Interneuronsmentioning
confidence: 99%